Comparative Metagenomics Reveals Microbial Signatures of Sugarcane Phyllosphere in Organic Management - Khoiri, Ahmad Nuruddin; Cheevadhanarak, Supapon; Jirakkakul, Jiraporn; Dulsawat, Sudarat; Prommeenate, Peerada; Tachaleat, Anuwat; Kusonmano, Kanthida; Wattanachaisaereekul, Songsak; Sutheeworapong, Sawannee (Frontiers in Microbiology, 2021)
Converting conventional farms to organic systems to improve ecosystem health is an emerging trend in recent decades, yet little is explored to what extent and how this process drives the taxonomic diversity and functional capacity of above-ground microbes. This study was therefore conducted to investigate the effects of agricultural management, i.e., organic, transition, and conventional, on the structure and function of sugarcane phyllosphere microbial community using shotgun metagenomics approach. Comparative metagenome analysis exhibited that farming practices strongly influenced taxonomic and functional diversities, as well as co-occurrence interactions of phyllosphere microbes. A complex microbial network with the highest connectivity was observed in organic farming, indicating strong resilient capabilities of its microbial community to cope with the dynamic environmental stressors. Organic farming also harbored genus Streptomyces as the potential keystone species, and plant growth-promoting bacteria as microbial signatures, including Mesorhizobium loti, Bradyrhizobium sp. SG09, Lactobacillus plantarum, and Bacillus cellulosilyticus. Interestingly, numerous toxic compound-degrading species were specifically enriched in transition farming, which might suggest their essential roles in the transformation of conventional to organic farming. Moreover, conventional practice diminished the abundance of genes related to cell motility and energy metabolism of phyllosphere microbes, which could negatively contribute to lower microbial diversity in this habitat. Altogether, our results demonstrated the response of sugarcane-associated phyllosphere microbiota to specific agricultural managements that played vital roles in sustainable sugarcane production.